2013
DOI: 10.1002/ceat.201300081
|View full text |Cite
|
Sign up to set email alerts
|

Design and Experimental Investigation of Calcium Looping Process for 3‐kWth and 1.9‐MWth Facilities

Abstract: The calcium looping CO2 capture process using calcium oxide as a regenerable solid sorbent has been under development at the Industrial Technology Research Institute (ITRI) of Taiwan for several years. The 3‐kWth test facility built at ITRI is mainly composed of a fluidized‐bed carbonator and a rotary kiln calciner. The calcination efficiency, the CO2 capture efficiency, and operating stability were investigated. In addition, a cold model test facility has been constructed and a 1.9‐MWth pilot plant designed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(44 citation statements)
references
References 18 publications
1
43
0
Order By: Relevance
“…The transport of solid material takes place via a pneumatic conveying link. To ensure smooth solid flow and prevent mixing of gases between the two reactors, a series of tanks are used (Chang et al, 2013). Lab-scale experiments with this design have shown promising results, with high CO 2 capture, close to the equilibrium capture efficiency.…”
Section: The 200 Kw Th Pilot Plant At the University Of Stuttgartmentioning
confidence: 96%
See 4 more Smart Citations
“…The transport of solid material takes place via a pneumatic conveying link. To ensure smooth solid flow and prevent mixing of gases between the two reactors, a series of tanks are used (Chang et al, 2013). Lab-scale experiments with this design have shown promising results, with high CO 2 capture, close to the equilibrium capture efficiency.…”
Section: The 200 Kw Th Pilot Plant At the University Of Stuttgartmentioning
confidence: 96%
“…The INCAR-CSIC facility reported a maximum capture efficiency of 90% (Alonso et al, 2010), while the CANMET facility and Stuttgart facility reported 94% (Lu et al, 2008) and 93% , respectively. Chang et al (2013) Later, Ohio State University (Wang et al, 2010), Tsinghua University (Fang et al, 2009), and ITRI (Chang et al, 2013) successfully demonstrated process feasibility. As a result of their simplicity, lab-scale plants were used for detailed parametric studies.…”
mentioning
confidence: 89%
See 3 more Smart Citations